Pengaruh Equity Merek Terhadap Keputusan Pembelian Mie Instan Di Kalangan Mahasiswa Kota Medan - Marbun, Nurpika; Sianturi, Charles M.; Simangunsong, Ridhon NB. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
The objective of this research to measure brand equity on purchasing decisions, using quantitative research methods. The location of the study was in Medan City, with respondents totaling 100 respondents who consume instant noodles. Data collection was carried out by distributing questionnaires, using a Likert Scale. Data were processed using SPSS version 26. Data analysis using multiple linear regression, and the results of data analysis showed that the multiple regression coefficient of variable X1, (Brand Awareness) is 0.076, variable X2, (Brand Association) is 0.139, variable X3, (Perceived Quality), is 0.098, variable X4, (Brand Loyalty) is 0.775 and the R square value is 0.590. It can be concluded that brand awareness, brand association, perceived quality, and brand loyalty have a positive and significant effect on purchasing decisions both through partial tests (t-test) and simultaneous tests (F-test).